AREA UNDER THE CURVES, VOLUME OF ROTATED, AND SURFACE AREA ROTATED ABOUT SLANTED LINE - Suandito, Billy (International Journal of Applied Sciences and Smart Technologies, 2020)
In the Calculus, a definite integral can be used to calculate the area between curves and coordinate axes at certain intervals; surface area and volume formed if an area is rotated against the coordinate axis. Problems arise if you want to calculate the area of the area bounded by a curve and a line that does not form an angle of 0 or 90 degree to the coordinate axis, as well as the calculation of the volume of objects and the surface area of a revolution axis of rotation is a slanted line. By using existing definitions, a formula is developed for this purpose.